The Effect of Basel III Liquidity, Credit Risk, and Market Risk on the Profitability of Commercial Banks in Indonesia - Mahisi, Pratisyara Puspa Widitha Narindra; Usman, Bahtiar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to analyze the effect of Basel III liquidity provisions, credit risk, and market risk on banking profitability in Indonesia. The global financial crisis has hit the banking world several times, showing that the fulfillment of capital requirements is not enough to make banks survive, so the Basel Committee on Banking Supervision initiated Basel III which added provisions regarding banking liquidity, namely Liquidity Coverage Ratio and Net Stable Funding Ratio. Previous research only discussed the effect of the Liquidity Coverage Ratio on banking profitability (Return on Assets and Net Interest Margin), with two control variables Equity to Assets Ratio and Bank Size. This study adds other independent variables of Basel III liquidity provisions (Net Stable Funding Ratio), credit risk (Non-Performing Loan), and market risk (Stock Return Risk). With a sample of 20 conventional banks listed on the IDX for the 5 years (2018-2022), 100 secondary data were obtained from each bank's website. The results of panel data regression with multiple regression analysis show that Net Stable Funding Ratio and Stock Return Risk only has a significant effect on Net Interest Margin; Non-Performing Loan and Bank Size have a significant effect on Return on Assets and Net Interest Margin; Equity to Assets Ratio only has a significant effect on Return on Assets; and Liquidity Coverage Ratio has insignificant effect on both Return on Assets and Net Interest Margin. This study provides implications for bank management and regulators to commit and supervise the NPL level low, and to provide support to increase bank assets.